The Influence of Hospital Volume on the Outcomes of Nasopharyngeal, Sinonasal, and Skull-Base Tumors: A Systematic Review of the Literature - Flukes, Stephanie; Sharma, Rahul K.; Lohia, Shivangi; Cohen, Marc A. (Journal of Neurological Surgery Part B: Skull Base, 2021)
Objective The center of excellence model of health care hypothesizes that increased volume in a specialized center will lead to better and more affordable care. We sought to characterize the volume-outcome data for surgically treated sinonasal and skull base tumors and (chemo) radiation-treated nasopharyngeal malignancy.Design  Systematic review of the literature.Setting This review included national database and multi-institutional studies published between 1990 and 2019.Participants PubMed was interrogated for keywords “hospital volume,” “facility volume,” and outcomes for “Nasopharyngeal carcinoma,” “Sinonasal carcinomas,” “Pituitary Tumors,” “Acoustic Neuromas,” “Chordomas,” and “Skull Base Tumors” to identify studies. Single-institution studies and self-reported surveys were excluded.Main outcome measures The main outcome of interest in malignant pathologies was survival; and in benign pathologies it was treatment-related complications.Results A total of 20 studies met inclusion criteria. The average number of patients per study was 4,052, and ranged from 394 to 9,950 patients. Six of seven studies on malignant pathology demonstrated improved survival with treatment in high volume centers and one showed no association with survival. Ten of thirteen studies on benign disease showed reduced risk of complications, while one study demonstrated both an increased and decreased association of complications. Two studies showed no volume-outcome associations.Conclusion This systematic review demonstrates that a positive volume–outcome relationship exists for most pathologies of the skull base, with some exceptions. The relative dearth of literature supports further research to understand the effect of centralization of care on treatment outcomes.
Keywords: volume outcomes; skull base; nasopharyngeal carcinoma; sinonasal carcinoma; pituitary; acoustic neuroma